Strategi Pengayaan Berbasis Digital Membaca Cepat Dan Pemahaman Dengan Aplikasi Quizizz di SD Negeri Belitung Selatan 1 Banjarmasin: Speed Reading And Comprehension Digital Enrichment Strategy With Quizizz Application At SD Negeri Belitung Selatan 1 Banjarmasin - Ratna Restapaty; Gusti Hanifah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The development of digital-based learning media is an excellent alternative in the attempt to enhance quality of education, especially learning Indonesian language and literature in elementary schools after the Covid-19 pandemic. The study's objectives were to (1) analyze the factors that influence students' motivation for reading habituation using quizizz digital media, 2) analyze the implementation of the quizizz application in the implementation of learning enrichment in the post-Covid-19 pandemic, and 3) learn about just a variety of advantages and disadvantages obtained by teachers and students through the provision of enrichment using the quizizz application. The research method employs a qualitative approach, a descriptive qualitative method. Purposive sampling was used in the study, with the research subject being a teacher who had utilized the Quizizz application in the learning process. The speed reading ability of grade V and VI elementary school students was the focus of this study. The results of this study show that this enrichment strategy is feasible for use as a learning innovation; however, this research is limited to the enrichment stage. The findings of this study are expected to serve as a model for schools in terms of using digital enrichment media quizzes to enhance student' speed reading and comprehension skills in Indonesian courses